2021
DOI: 10.1016/j.jamda.2021.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Profit Margins and Citations for Infection Prevention and Control

Abstract: Objectives Recent rampant spread of COVID-19 cases in nursing homes has highlighted the concerns around nursing homes’ ability to contain the spread of infections. The ability of nursing homes to invest in quality improvement initiatives may depend on resource availability. In this study, we sought to examine whether lower profit margins, as a proxy for lack of resources, are associated with persistent infection control citations. Design We conducted a retrospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Similarly, a study has noted that training is important to avoid medication errors in assisted living facilities 10 . In the nursing home industry, we have evidence that low staffing levels, lack of training and education, and lower profit margins are associated with deficiency citations 11–13 …”
Section: Introductionmentioning
confidence: 82%
“…Similarly, a study has noted that training is important to avoid medication errors in assisted living facilities 10 . In the nursing home industry, we have evidence that low staffing levels, lack of training and education, and lower profit margins are associated with deficiency citations 11–13 …”
Section: Introductionmentioning
confidence: 82%
“…(87) Likewise, total nurse staffing levels (all grades of nurse staff) and compliance were positively associated in eleven studies (36,45,51,54,87,110,111,128,153,156,158) , with two finding a negative association (49,111) and three a null association. (37,72,84) The results are similar for nurse aides/care assistants: 15 studies reported higher levels these staff and compliance were positively associated (15,35,37,48,49,51,54,56,58,79,90,126,128,138,154,156) , nine reported a null association (16,52,61,88,89,110,113,120,155) and three reported a negative association. (45,47,57) A higher ratio of registered nurses as against other nurse and care staff and compliance was positively associated in four studies (92,…”
Section: Other: Staffingmentioning
confidence: 74%
“…(36,45,48,159) Higher levels of licensed practitioner/vocational nurses and compliance were positively associated in five (54,56,57,70,154) , negative in five (45,47,48,51,106) , and a null association reported in 13. (15,49,52,58,61,79,88,89,110,113,120,138,156) Higher specialist staff levels (e.g. dietary professionals) and compliance were positively associated in five studies (15,35,81,154,160) , negative in one (118) ; and null in two.…”
Section: Other: Staffingmentioning
confidence: 96%
See 2 more Smart Citations